2020
DOI: 10.36849/jdd.2020.10.36849/jdd.2020.4684
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Painful Cutaneous Vasculopathy With Rivaroxaban in a Patient With Systemic Lupus Erythematosus

Abstract: Novel oral anticoagulant (NOAC) medications have revolutionized hematology and cardiology. Recently, NOACs have demonstrated additional promise in dermatology. Specifically, rivaroxaban, a direct factor Xa inhibitor NOAC, has been shown to be successful in the treatment of livedoid vasculopathy. Herein, we describe a patient with systemic lupus erythematosus who presented with painful cutaneous vasculopathy, demonstrated on biopsy with occlusive microvascular fibrin thrombi without evidence of concurrent vascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Table 3 shows the articles from our review of the literature for studies that reported on anticoagulant treatment in LV patients (4 prospective studies, 2 retrospective studies, and 33 case reports) 2,5‐42 . From 39 studies, 219 patients with 139 (63.5%) females and 80 (36.5%) males were included.…”
Section: Resultsmentioning
confidence: 99%
“…Table 3 shows the articles from our review of the literature for studies that reported on anticoagulant treatment in LV patients (4 prospective studies, 2 retrospective studies, and 33 case reports) 2,5‐42 . From 39 studies, 219 patients with 139 (63.5%) females and 80 (36.5%) males were included.…”
Section: Resultsmentioning
confidence: 99%
“…After a comprehensive assessment by two independent reviewers, 12 studies, case series, and case reports as well as one clinical trial were included. 5,[8][9][10][11][12][13][14][15][16][17][18][19] The studies were from the United States, the United Kingdom, Korea, Germany, China, and Brazil. The following data were extracted from each article: authors, year, country, number of patients, age, gender, comorbidities, thrombophilic factors, previous treatments, combination treatments, dose of rivaroxaban, treatment duration, efficacy, recurrence, and side effects (Tables 1 and 2).…”
Section: Resultsmentioning
confidence: 99%
“…In total, 22 articles and one registered clinical trial were identified from the PubMed, Cochrane, and Embase databases using the search strategy described above. After a comprehensive assessment by two independent reviewers, 12 studies, case series, and case reports as well as one clinical trial were included 5,8–19 . The studies were from the United States, the United Kingdom, Korea, Germany, China, and Brazil.…”
Section: Resultsmentioning
confidence: 99%
“…Rivaroxaban is a direct factor Xa inhibitor used to prevent stroke in atrial fibrillation as well as to treat and prevent venous thromboembolism [ 12 ]. It is a medicine with predictable pharmacokinetics and pharmacodynamics, as well as possessing a fast onset of action.…”
Section: Reviewmentioning
confidence: 99%
“…Rivaroxaban was started at 20 mg once daily for a patient with SLE. Within two months of treatment, the patient's foot discomfort and discoloration were gone, and she no longer needed narcotic pain medication [ 12 ]. Combination treatment also proves effective in the treatment of LV.…”
Section: Reviewmentioning
confidence: 99%